Dual Ectopic Thyroid: A Case Report in a 12 years old girl (Bangladesh Journal of Nuclear Medicine, 2022)
Ectopic thyroid gland is uncommon in our routine clinical practice and among them dual ectopic thyroid appears to be rarer. We report an unusual case of two different locations of ectopic thyroid tissues in the lingual and left submandibular regions of a 12 years old girl who presented with painless, nodular left upper neck swelling. Provisionally, the patient was diagnosed by high resolution ultrasound (HRUS) of neck and confirmed by radionuclide thyroid scan. Thyroid scintigraphy with 99mTc-pertechnetate is highly sensitive but minimally invasive procedure to detect and image the ectopic thyroid tissue with fairly good specificity and negligible radiation exposure.Bangladesh J. Nuclear Med. 23(1&2): 67-69, 2020